1991
DOI: 10.1139/v91-277
|View full text |Cite
|
Sign up to set email alerts
|

The proton affinities and deprotonation enthalpies of β-D-fructopyranose and α-L-sorbopyranose

Abstract: The proton affinities (PAS) and deprotonation enthalpies (DPEs) were calculated for the pyranoid forms of two naturally occumng sugars, D-fructose and L-sorbose. In both molecules the PAS of the primary hydroxyl group (HO-1), the anomeric hydroxyl group (HO-2), and the ring-oxygen atom (0-6) were calculated, as were the DPEs of HO-1 and HO-2. The stabilities of the conjugate acids and bases of these sugars are enhanced by the presence of intramolecular hydrogen bonding, a feature that is significant in explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“… 19 , realizing the “one-pot” synthesis of HMF from glucose with relatively high conversion and selectivity. On the other hand, glucose has lower acidity than fructose 20 21 22 23 and hence is less reactive under basic conditions. Recently, Liu et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , realizing the “one-pot” synthesis of HMF from glucose with relatively high conversion and selectivity. On the other hand, glucose has lower acidity than fructose 20 21 22 23 and hence is less reactive under basic conditions. Recently, Liu et al .…”
mentioning
confidence: 99%
“…D-glucose (monomer of cellulosic biomass) and D-fructose (pivotal intermediate for cellulose utilization), in both α- and β-anomers, have been considered. To best of our knowledge, all previous sugar conversions focused on O sites, which are preferred over C sites during protonation 16 17 18 36 37 38 and deprotonation 20 21 22 23 . Here a systematic study was also conducted for O-centered sugar radicals, and comparisons with the results of C-centered radicals clearly indicated that the formation of C-centered radicals is always preferential, thus suggesting the possibility to activate and convert the C-H bonds of biomass sugars.…”
mentioning
confidence: 99%